Kontribusi Daya Ledak Otot Tungkai Dan Daya Ledak Otot Lengan Terhadap Kemampuan Smash Bolavoli Club Remapon Kecamatan Kampar - Ariando Ashar (Pusat Pengembangan Olahraga Universitas Pahlawan, 2026)
The purpose of this research is to look for how to contribute the explosive power leg muscle and explosive power arm muscle to smash ability of the Remapon volleyball club. This type of research is a correlation that aims to find there is no relationship and if there is any relationship and meaning or absence of the relationship. The research population is the men of the Remapon volleyball club, which amounted to 15 people. Sampling techniques are a total sampling. The research instrument uses a Vertical Jump test, medicine ball test and volleyball smash test. The results of of research is the Contribution of the explosive power leg muscle to smash ability of 64%, Contribution of the explosive power arm muscle to smash ability of 70,6% and Contribution of explosive power leg muscle and explosive power arm muscle together to smash ability of 86,49% The conclusion, there is any Contribution of the explosive power leg muscle to smash ability, Contribution of the explosive power arm muscle to smash ability and Contribution of explosive power leg muscle and explosive power arm muscle together to smash ability of the Remapon volleyball club.